Effect of Plyometric Hurdle Hops and Tuck Jump Training on Strength and Leg Muscle Power in Martial Arts Athletes at Kostrad Company-C Malang - Shidqi Hamdi Pratama Putera; Hari Setijono; Oce Wiriawan (BIRCU, 2019)
The purpose of this study was to analyze the effect of hurdle hops and tuck jump exercises on leg muscle strength and power, as well as the different effects of hurdle hops and tuck jump exercises on leg muscle strength and power. The research method used in this study is quantitative with quasi-experimental methods, with the design of this study using a non-randomize control group pretest and posttest design, with data analysis using ANOVA. The process of data retrieval is done by testing the leg muscle strength using a strength test tool that is a leg dynamometer and leg muscle power test with a jump md, during the pretest and posttest, then the data are analyzed using SPSS 22.0 series. The target of this study was martial arts athlete Kostrad Company-C with 30 members, divided into 3 groups with each group totaling 10 people, this research was conducted for 6 weeks. Paired sample strength test results and paired sample test of leg muscle power test that the significance level of each variable obtained sig 0,000 <0.05 thus there is a significant influence or difference between the pretest and posttest of the dependent variables of leg muscle strength and power, ANOVA test results on leg muscle strength and strength, showing strength, F: 12,191, sig 0,000, Power F: 4,778, sig 0.17, so it can be concluded that there are significant differences in the results of leg muscle strength and strength in three different groups, because sig <0.05. From the results of the post hoc multiple comparations (LSD) test of independent variables that have a significant influence on the increase in the dependent variable, it can be seen from the mean different results that the hurdle hops group gained 31,900 strength, power 155,367,00, meaning that the hurdle hops exercise was more influential. Based on the above analysis it can be concluded that there is an increase in leg muscle strength and power for each group, through the ANOVA test. Where hurdle hops exercises have a better effect than tuck jump exercises and the control group on leg muscle strength and power.